Improving the technological and nutritive properties of gluten-free bread by fresh curd cheese enrichment - Graça, Carla (2020)
Replacing wheat flour in the breadmaking process is a technology challenge since the elimination of gluten has a strong influence on bread quality. Proteins addition are often used to form a protein network capable of mimicking gluten-like structure, giving to dough a foaming support. This study aimed to evaluate the potential of denatured whey proteins coming from fresh curd cheese addition, to strengthening gluten-free dough structure, enhancing the breadmaking performance. Curd cheese additions were tested (5% up to 20%, weight/weight) and the e ect on dough rheology behavior and bread quality was evaluated. Findings obtained revealed that the technology and nutritional properties of the bread can be enhanced by curd cheese addition, and such e ects should be related to the composition and functionality of denatured whey proteins. Considering higher levels of curd cheese (20%) tested, improvements on bread quality was observed, leading to a considerable increase in bread volume (73%), softness (65%), with a significant reduction on staling kinetics (70%), comparing with control bread. Additionally, an improvement in nutritional value in terms of proteins (80%) and minerals content (P—50.0%, Mg—6.0%, and Ca—360.3%) was obtained, which can give an additional contribution to the nutritional daily requirements of celiac patients. Linear correlations between dough rheology properties and bread quality attributes were found, supporting the good breadmaking performance obtained